The Collection System of Eye Movements for Psychological Disorder - Kim, Dong Hyun; Lee, Hyun Woo; Lee, Young Sil (International Journal of Psychosocial Rehabilitation, 2020)
ADHD is one of the psychological disorder of children and the national health insurance of korea reported the 55,000 of infants and children have ADHD in 2014. Since the features of ADHD lead to various side effects, such as the learning disability, memory ability, it is required to diagnose ADHD in childhood and start the treatment of ADHD. However, it is difficult to diagnose ADHD in childhood if the child does not show the hyperactivity symptom. Also, since the questions are too professional or the diagnosis test requires the cognitive and activity abilities, the children have the difficulties to understand the questions and show the proper response. To solve this problem, we propose the collection system of eye movements for ADHD diagnosis. The proposed system displays four types of korean texts: a letter, a word, a sentence and a paragraph. When a subject watches the sample texts, the system collects the coordinates and time of eye movements and transforms them into gaze pattern data for ADHD diagnosis. The benefit of the proposed system is that the physical interventions for the subject are not required to collect the diagnosis data during the assessment for ADHD.